2020
DOI: 10.1007/s40588-020-00152-6
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Arthritis: Update

Abstract: Purpose of Review The aim of this paper is to provide an overview about reactive arthritis, with an update regarding pathophysiology and therapeutic approach of the disease, outlining the clinical features and diagnostic approach, based on recent literature review. Recent Findings Reactive arthritis is considered to be part of the spectrum of the spondyloarthritis. Its epidemiology is changing worldwide due to several reasons, among them are as follows: different diagnosis approach and clinical presentations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 60 publications
1
24
0
2
Order By: Relevance
“…ReA is diagnosed more frequently in young adults and it has been revealed that cases are concentrated between the ages of 18 and 40 years [ 39 ]. The median age of ReA cases after COVID-19 was seen to be 50 years and was considered to be slightly higher than the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…ReA is diagnosed more frequently in young adults and it has been revealed that cases are concentrated between the ages of 18 and 40 years [ 39 ]. The median age of ReA cases after COVID-19 was seen to be 50 years and was considered to be slightly higher than the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…ReA concept is a recent object of revisiting, especially through the observed epidemiological reduction of sex-transmitted disease in high-income countries as well as recognition of miscellaneous pathogens responsible for the disease. [ 12 , 13 ] Among miscellaneous responsible pathogens, some viruses are enlisted and the first COVID-19-related ReA cases start to emerge, [ 10 ] as we aforementioned.…”
Section: Discussionmentioning
confidence: 99%
“…He reported having had reactive arthritis after enteric Salmonella infection more than 30 years ago. Although determination of HLA-B27 was not done at that time, an association between this phenotypic marker and reactive arthritis is well known making it likely that the patient’s tendency to develop reactive arthritis after infection with defined intestinal pathogens (e.g., Salmonella enterica and C. difficile ) is at least partially linked to HLA-B27 ( Bentaleb et al, 2020 ). Even if this evidence attaches a role to HLA-B27 in the development of post-infectious reactive arthritis, only 59% of the described patients were positive for this biomarker ( Table 1 ), making its precise involvement in pathogenesis still debatable ( Bentaleb et al, 2020 ).…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%